Femtosecond Laser Assisted Keratoplasty - Devesh Sharma; Umang Mathur (Delhi Journal of Ophthalmology)
Femtosecond lasers have a wide variety of applications in anterior segment surgery. The technology has also been used for lamellar and penetrating keratoplasties. Graft-host misalignment frequently occurs with conventional penetrating keratoplasty that leads to significant post-operative astigmatism. Improved wound designs with the femtosecond laser-mushroom, top-hat, zig-zag, Christmas tree, and dovetail, increase the surface area of apposition and provide more secure incisions. Early visual rehabilitation and suture removal are possible advantages. Lesser post-operative astigmatism has also been reported. Deep anterior lamellar keratoplasty with the femtosecond laser (FDALK) may help reduce intra-operative complications like perforation of the Descemet's membrane. Incision designs similar to penetrating grafts are used. Femtosecond laser assisted anterior lamellar keratoplasty (FALK) is useful for superficial corneal scars and dystrophies. Sutureless replacement of the anterior corneal stroma greatly enhances visual rehabilitation and limits induced post-operative astigmatism. Additional procedures like photo-refractive keratectomy (PRK) may be performed for refractive errors, post-operatively. Femtosecond laser assisted endothelial keratoplasty (FLEK) has been used to cut donor discs. However, deep in the corneal stroma, microkeratomes give smoother cuts. Disadvantages with this technology include increased cost, longer operative time, and logistics. However, the precision and accuracy of the femtosecond laser has the potential to overcome many of the problems faced with conventional corneal transplant procedures.